A simple method for measuring crosstalk in stereoscopic displays - Weissman, M.; Woods, Andrew (2011)
Crosstalk (also known as "ghosting", "leakage", or "extinction"), a vitally important concept in stereoscopic 3D displays, has not been clearly defined or measured in the stereoscopic literature (Woods). In this paper, a mathematical definition is proposed which uses a "physical" approach. This derivation leads to a clear definition of leftview or right-view crosstalk and shows that 1), when the display's black level is not zero, it must be subtracted out and 2), when the source intensities are equal, crosstalk can be measured using observed intensities totally within the respective view. Next, a simple method of measuring crosstalk is presented, one that relies on only viewing a test chart on the display. No electronic or optical instruments are needed. Results of the use of the chart are presented, as well as optical measurements, which did not agree well with chart results. The main reason for the discrepancy is the difficulty of measuring very low light levels. With wide distribution, this tool can lead to the collection of useful performance information about 3D displays and, therefore, to the production of the best stereoscopic displays.